KEBUTUHAN NUTRISI CRUSTACEA DAN POTENSI CACING LUR (NEREIS, POLYCHAETA) UNTUK PAKAN UDANG NUTRITION REQUIREMENT OF CRUSTACEAN AND THE POTENTIAL OF RAGWORM (NEREIS, POLYCHAETA) FOR FEED OF SHRIMP - Yuwono, Edy (Pembangunan Pedesaan, 2005)
Knowledge on nutrition aspect is essential in aquacultural development. Information on crustacean nutritional requirement have been substantially abundance and needed to be critically reviewed. The potency in term of nutritional content of ragworm Nereis and itâs use for feed of shrimp have been reported in many papers. The worm contains different macromolecule and amino acid as well as fatty acid required for optimum growth and reproduction of shrimp. Therefore, the worm is nutritionally appropriate for feed of shrimp.